Studi Pemanfaatan Abu Sekam Padi sebagai Bahan Pengisi dalam Pembuatan Beton: Study on the Utilization of Rice Husk Ash as a Filler Material in Concrete Production - Yoel, Jerry Andre Cluiver; Sahusilawane, Tonny; Apalem, Delvia Rimesye (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Waste accumulation is an environmental issue that is still commonly found in society. The accumulation that occurs in the waste is caused by suboptimal waste processing. One of the most commonly found types of waste is agricultural waste, especially in rural areas, such as rice husk ash waste. From the collection site, it can be found in areas with rice fields. From the results of this research, it was found that for the normal quality mix, the compressive strength was 14.81 MPa, while the 5% mix had a strength of 14.64 MPa, and the 10% and 15% mixes experienced a decrease to 13.49 MPa and 13.67 MPa, respectively. For this research, cylindrical test specimens with a diameter of 15 cm and a height of 30 cm were used, with testing ages of 7 and 14 days.